2009
DOI: 10.1007/s10396-009-0211-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular diastolic function using color kinesis: differentiation between normal and pseudonormalized patterns

Abstract: The analysis of diastolic CK with ICK software is a useful method for detecting delayed early diastolic relaxation. We concluded that diastolic CK images may be applied to differentiating between normal and pseudonormalized patterns of LV inflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…They reported that delayed early diastolic relaxation and dyssynchrony, which are considered to be caused by myocardial ischemic memory, can be detected using CK-DI [31][32][33]. We have previously reported that this CK-DI is superior in reproducibility, can be applied to quantitative evaluation of LV global diastolic function, and to differentiating between normal and pseudonormalized patterns of LV inflow [22,23]. Takeda et al confirmed the significant correlation of tau with CK-DI of the whole heart, not with E/A, using an animal diastolic heart failure model [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that delayed early diastolic relaxation and dyssynchrony, which are considered to be caused by myocardial ischemic memory, can be detected using CK-DI [31][32][33]. We have previously reported that this CK-DI is superior in reproducibility, can be applied to quantitative evaluation of LV global diastolic function, and to differentiating between normal and pseudonormalized patterns of LV inflow [22,23]. Takeda et al confirmed the significant correlation of tau with CK-DI of the whole heart, not with E/A, using an animal diastolic heart failure model [34].…”
Section: Discussionmentioning
confidence: 99%
“…Color kinesis (CK) is a real-time echocardiographic technique based on acoustic quantification that yields regional and global information on the magnitude and timing of LV wall motion by tracking and color-encoding endocardial motion throughout the cardiac cycle [18][19][20][21]. We previously reported that the analysis of diastolic CK is a useful method for quantitative evaluation of LV diastolic function and detecting delayed LV relaxation [22,23]. The aim of this study is to investigate the relationship between plasma BNP levels and LV diastolic function by using diastolic CK imaging.…”
Section: Introductionmentioning
confidence: 99%